Quadrupole mass spectrometry and its applications - Dawson, Peter H. (Elsevier Scientific Pub. Co., 1976)
Quadrupole Mass Spectrometry and Its Applications provides a comprehensive discussion of quadrupoles and their applications. It proceeds from a general explanation of the action of radiofrequency quadrupole fields to the description of their utilization in mass analyzers-such as the quadrupole mass filter, the monopole, the three-dimensional quadrupole ion trap, and various time-of-flight spectrometers-and finally to the characteristic applications of quadrupoles. A multi-author format has been adopted to provide broader-than-usual viewpoint in the book. The book begins by explaining the princ.